“Tem aqui na escola, perto de casa, em todo lugar”: percepções de jovens estudantes de Aparecida de Goiânia sobre as relações entre educação escolar e violência - Silva, Frederiko Luz (2022)
The present thesis is the result of an exploratory study developed in the Graduate Program in Education of the Faculty of Education of the Federal University of Goiás – PPGE/FE/UFG, in the research line State, Policies and History of Education, on the theme Perceptions of young students from Aparecida de Goiânia on the relation between school education and violence. Its general objective was to analyze, based on the listening of the young participants, the relationship between violence and age/grade distortion. The main methodological resource used for data collection was the holding of talking circles with students from four schools in the municipality of Aparecida de Goiânia, enrolled in 9th grade classes of Elementary School. The discussion about the data was theoretically based on Critical Discourse Analysis. We sought to develop the study from the perspective of the Sociology of Youth, understanding young people as active social subjects, beyond the simplistic conception based on age delimitation - used by legal apparatus. From the analysis of the speeches of the research participants, it was noticed that the inequality in the offer of quality in education is a strong element that generates school failure, identified both in the presence of 15-year-old students still in Elementary School, and in the relation of students with the violence they practice and which affects them inside and outside school walls. The school environment is also configured as an environment of violence, since the profile of the young people surveyed coincides with the profile of a (constructed) social enemy, vulnerable to the death policies of the State – of killing and letting die. The age-grade distortion needs to be faced in the complex dynamics of young people's lives in which, among other elements, the violence experienced is an important factor in their practices and perception of the future.